Detection of IgG Antibodies for gp51-Bovine Leukemia Virus in Cattle and Water Buffaloes by Application of ELISA Technique - Al-Galebi, Ahlam Ali Soghi (Al-Qadisiyah Journal of Pure Science, 2018)
The main objective of this study was to detect the seroprevalence of specific IgG-antibodies against bovine leukemia virus antigen (BLV-gp51-Ab) in cattle and buffaloes of some areas in Al-Qadisiyyah governorate / Iraq, by using an indirect ELISA test manufactured by (VMRD, USA). Totally, 184 serum samples were collected from 135 cattle and 49 water buffaloes, which subjected to the study’s test. Also, the required data about study’s animals were obtained from owners and supervised veterinarians on some herds. The overall results appeared that 11.85 % of cattle were seropositively. While in buffalo, the seropositive results have been not achieved and the test result was (0%). In cattle, the correlation between seropositive results and a number of risk factors was estimated, and revealed that in age, breed and type of production factors, the significant increasing in seropositive prevalence were showed in > 3 years group that have (16.39 %), pure breed (19.35 %), and dairy cattle (15.38 %), respectively. Whilst, the significant differences within the groups related to both sex and herd management factors didn’t reported at a level of P£0.05.